Revealing the thermodynamic background of the memory effect in phase separating cathode materials - Zelič, Klemen (Strojniški vestnik, 2019)
Phase separating Li-ion battery cell cathode materials feature a well-known phenomenon called the memory effect. It manifests itself as an abnormal change in working voltage being dependent on cell cycling history. It was only recently that plausible mechanistic reasoning of the memory effect in Li-ion batteries was proposed. However, the existing literature does still not consistently reveal a phenomenological background for the onset or absence of the memory effect. This paper provides strong experimental and theoretical evidence of the memory effect in phase separating Li-ion battery cathode materials. Specifically, the background leading to the onset or absence of the memory effect and the underlying causal chain of phenomena from the collective particle-by-particle intra-electrode phenomena to macroscopic voltage output of the battery are presented and discussed. The results, clearly reveal that no memory effect is observed and predicted for low cut off voltages, whereas the absence of the first rest in memory writing cycle does not result in the absence of the memory effect, as previously believed. In addition, excellent agreement between the simulated and measured results is shown which, on one hand confirms the credibility of the combined analyses and, on the other, provides clear causal relations from macroscopic experimental parameters to simulated phenomena on the particle level.
Keywords: katodni material s fazno separacijo; Li-ion battery; litij ionske baterije; memory effect; multi-particle porous electrode; phase separating material; spominski efekt; večdelčna porozna elektroda